Binding of Tissue Plasminogen Activator to Vascular Grafts - Harvey, Richard A; Kim, Hugh C; Pincus, Jonathan; Trooskin, Stanley Z; Wilcox, Josiah N; Greco, Ralph S (Thrombosis and Haemostasis, 1989)
Tissue plasminogen activator labeled with radioactive iodine (125I-tPA) was immobilized on vascular prostheses chemically modified with a thin coating of water-insoluble surfactant, tridodecylmethylammonium chloride (TDM AC). Surfactant- treated Dacron, polytetrafluoroethylene (PTFE), silastic, polyethylene and polyurethane bound appreciable amounts of 125I- tPA (5-30 μg 125I-tPA/cm2). Upon exposure to human plasma, the amount of 125I-tPA bound to the surface shows an initial drop during the first hour of incubation, followed by a slower, roughly exponential release with a t½ of appoximately 75 hours. Prostheses containing bound tPA show fibrinolytic activity as measured both by lysis of clots formed in vitro, and by hydrolysis of a synthetic polypeptide substrate. Prior to incubation in plasma, tPA bound to a polymer surface has an enzymic activity similar, if not identical to that of the native enzyme in buffered solution. However, exposure to plasma causes a decrease in the fibrinolytic activity of both bound tPA and enzyme released from the surface of the polymer. These data demonstrate that surfactant-treated prostheses can bind tPA, and that these chemically modified devices can act as a slow-release drug delivery system with the potential for reducing prosthesis-induced thromboembolism.
Keywords: Tissue plasminogen activator; Thrombolysis; Surfactant; Tridodecylmethylammonium chloride